My mother was nuts : a memoir - Marshall, Penny (Harvest/Houghton Mifflin Harcourt, 2012)
From her humble roots in the Bronx to "Laverne and Shirley" and her unlikely ascent in Hollywood, the beloved actor and director tells the story of her incredible life.